HIV-associated CD8+ encephalitis confirmed by cerebrospinal fluid flow cytometry: first case in Colombia - Soto-Moreno, Nicolas; Pinzon, Nicole; Echandia, Natalia; Rojas-Tabares, Omar; Yanguma, Marcela; Oviedo, Laura; Ariza-Varón, Michael (Frontiers in Medicine, 2025)
IntroductionEncephalitis in patients with human immunodeficiency virus (HIV) can be caused by opportunistic infections, immune-mediated processes, or direct viral damage. CD8 + encephalitis is a rare condition. We report the first confirmed case in Colombia, diagnosed by cerebrospinal fluid (CSF) flow cytometry.Clinical caseA 50-year-old man with a history of liver cirrhosis and HIV, who had suspended antiretroviral treatment 1 month prior to admission, presented to the emergency department with a 2-day history of disorientation, bradyphrenia, dysarthria, and headache. Neurological examination revealed agitation, disorientation, language, memory, and abstraction difficulties, as well as ataxia and generalized chorea. The patient’s CD4 count was 838 cells. Brain magnetic resonance imaging (MRI) showed bilateral asymmetric leukoencephalopathy, and lumbar puncture revealed lymphocytic pleocytosis. After ruling out other differential diagnoses, flow cytometry confirmed the diagnosis of CD8 + encephalitis by identifying 42 cells (59.73% CD8+). The patient’s condition improved following the steroid treatment initiation.DiscussionCD8+ T-cell encephalitis is an uncommon immune-mediated disorder in HIV patients, typically occurring when the virus is controlled by antiretroviral therapy. Clinically, it can manifest as global impairment of consciousness, headache and focal symptoms. Diagnosis is typically made via brain biopsy, but imaging and other methods, such as flow cytometry, can be useful. Corticosteroids are the first-line treatment, and prognosis is highly variable.ConclusionCD8-mediated encephalitis is a rare condition that requires a complex diagnosis. We present a case of an HIV patient who responded well to corticosteroid therapy without the need for a brain biopsy, confirmed by flow cytometry.